Myxococcus xanthus DK1622 Coordinates Expressions of the Duplicate groEL and Single groES Genes for Synergistic Functions of GroELs and GroES - Zhuo, Li; Wang, Yan; Zhang, Zheng; Li, Jian; Zhang, Xiao-Hua; Li, Yue-zhong (Frontiers in Microbiology, 2017)
Chaperonin GroEL (Cpn60) requires cofactor GroES (Cpn10) for protein refolding in bacteria that possess single groEL and groES genes in a bicistronic groESL operon. Among 4861 completely-sequenced prokaryotic genomes, 884 possess duplicate groEL genes and 770 possess groEL genes with no neighbouring groES. It is unclear whether stand-alone groEL requires groES in order to function and, if required, how duplicate groEL genes and unequal groES genes balance their expressions. In Myxococcus xanthus DK1622, we determined that, while duplicate groELs were alternatively deletable, the single groES that clusters with groEL1 was essential for cell survival. Either GroEL1 or GroEL2 required interactions with GroES for in vitro and in vivo functions. Deletion of groEL1 or groEL2 resulted in decreased expressions of both groEL and groES; and ectopic complementation of groEL recovered not only the groEL but also groES expressions. The addition of an extra groES gene upstream groEL2 to form a bicistronic operon had almost no influence on groES expression and the cell survival rate, whereas over-expression of groES using a self-replicating plasmid simultaneously increased the groEL expressions. The results indicated that M. xanthus DK1622 cells coordinate expressions of the duplicate groEL and single groES genes for synergistic functions of GroELs and GroES. We proposed a potential regulation mechanism for the expression coordination.